Fluorimetric Determination of Nucleic Acid Using Enhancement of Terbium-gadolinium-2-thenoyltrifluoroacetone System - ZHEN, JIA (Asian Journal of Chemistry, 2010)
The fluorescence intensity of terbium-2-thenoyltrifluoroacetonenucleic acid system can be enhanced by Gd3+. Accordingly, a new method of determining nucleic acid was advanced. In the best conditions, the enhanced fluorescence intensity by nucleic acids was in proportion to the concentration of nucleic acids among the range of 5.0 ×10-8 g/mL to 3.0 × 10-5 g/mL for fish sperm DNA and 1.0 × 10-7 to 3.0 × 10-5 g/mL for yeast DNA. Their detection limits (S = N/3) were 4.8 and 9.0 ng/mL, respectively. The method was used for the determination of yRNA in sample and the result was quite satisfactory.